2011
DOI: 10.4061/2011/159621
|View full text |Cite
|
Sign up to set email alerts
|

Impact of External Cue Validity on Driving Performance in Parkinson's Disease

Abstract: This study sought to investigate the impact of external cue validity on simulated driving performance in 19 Parkinson's disease (PD) patients and 19 healthy age-matched controls. Braking points and distance between deceleration point and braking point were analysed for red traffic signals preceded either by Valid Cues (correctly predicting signal), Invalid Cues (incorrectly predicting signal), and No Cues. Results showed that PD drivers braked significantly later and travelled significantly further between d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
27
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 12 publications
(29 citation statements)
references
References 64 publications
2
27
0
Order By: Relevance
“…The review yielded 9 Class III studies. 6,9,14,[35][36][37][38][39][40] Conclusion. From the 9 Class III studies, we concluded that cognitive abilities may deteriorate even in mild to moderate stages of PD.…”
Section: Rating Article By Classmentioning
confidence: 99%
See 1 more Smart Citation
“…The review yielded 9 Class III studies. 6,9,14,[35][36][37][38][39][40] Conclusion. From the 9 Class III studies, we concluded that cognitive abilities may deteriorate even in mild to moderate stages of PD.…”
Section: Rating Article By Classmentioning
confidence: 99%
“…35 The use of external cues may help improve skills related to driving. 39 Recommendations. Level C: MMSE scores and contrast sensitivity (assessed via the Pelli-Robson Chart) are possibly predictive of simulated driving performance in the mild to moderate stages of PD.…”
Section: Rating Article By Classmentioning
confidence: 99%
“…This study combines data from the total samples (PD and control groups) of 2 separate but related studies for which we had collected data in 2004 (Stolwyk et al, 2005) and 2008 (Scally et al, 2011). Because these 2 studies used identical recruitment procedures, inclusion and exclusion criteria, cognitive assessments, and driving questionnaire content and administration, we could combine their data to increase statistical power.…”
Section: Participantsmentioning
confidence: 98%
“…While there is not yet sufficient evidence to determine whether drivers with PD have an abnormally high risk of car crashes (Adler et al, 2000;Charlton et al, 2010;Dubinsky et al, 1991;Uc et al, 2011), numerous studies have demonstrated impaired driving performance in both simulated (Scally et al, 2011;Stolwyk et al, 2005;Zesiewicz et al, 2002) and on-road (Heikkila et al, 1998;Uc et al, 2006aUc et al, , 2006bUc et al, , 2007Wood et al, 2005) environments. These driving difficulties have been detected even in the early stages of PD and linked to such disease and demographic variables as age, disease stage, motor impairment, visual problems, cognitive difficulties, and medication effects (Classen et al, 2011;Crizzle et al, 2012;Klimkeit et al, 2009).…”
mentioning
confidence: 97%
“…As a result, individuals with PD become overly reliant on visual/auditory external stimuli to guide skilled movement (Romero, Van Gemmert, Adler, Bekkering, & Stelmach, 2003). Converging evidence suggests marked improvement in performance with external cueing for behaviors such as walking (Luessi, Mueller, Breimhorst, & Vogt, 2012;Mak, Yu, & Hui-Chan, 2013), writing (Oliveira, Gurd, Nixon, Marshall, & Passingham, 1997Teulings, Contreras-Vidal, Stelmach, & Adler, 1997), and driving (Scally et al, 2011; Stolwyk, Triggs, Charlton, Lansek, & Bradshaw, 2005). …”
mentioning
confidence: 99%